Reconhecimento social e autonomia intersubjetiva: direito e inclusão da pessoa com deficiência no mercado de trabalho - Braga, Mariana Moron Saes [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The legislation of including disabled people in companies came into effect at the end of the 1980s. Due to the compulsory nature, as this legislation envisages fines and prison if not complied with, disabled people have been contracted by companies. This research was done in an attempt to analyze the inclusion process from the point of view of Axel Honneth’s recognition theory. The aim of this study is to analyze the level of social or intersubjective autonomy of disabled people and add components to build a model of understanding the vulnerability of disabled people. By intersubjective autonomy, we mean the web of social relationships of recognition (in which social subjects recognize and are recognized by others) which is inherent to the individual identity, ensuring self-confidence, self-respect and self-esteem. Visually impaired people working in the job market were selected. Semi-directive interviews were used as a technique to collect data from individual interviews. The aim was to identify the experience of intersubjective autonomy that the subjects had gained in social relationships of affection, juridical recognition and esteem. Based on the results, it can be concluded that the use of legislation was positive for almost all the subjects in terms of developing relationships of recognition parallel to work inclusion. Although the data showed legislation efficiency in terms of the subjects gaining in relation to acquisition and/or maintaining self-confidence, self-esteem or self-respect, new studies could help reflect on improving conditions of implementing the inclusion legislation and its social effects.
Keywords: Deficiência - Aspectos sociais; Deficientes - Estatuto legal, leis, etc; Mercado de trabalho; Inclusão social; Autonomia intersubjetiva; Deficiency; Social recognition; Intersubjective autonomy; Inclusion legislation; Critical theory